Hotspots for SARS‐CoV‐2 Omicron variant spread: Lessons from New York City. Issue 7 (14th March 2022) - Ramírez, Juan D.; Castañeda, Sergio; Ballesteros, Nathalia; Muñoz, Marina; Hernández, Matthew; Banu, Radhika; Shrestha, Paras; Chen, Feng; Shi, Huanzhi; van Bakel, Harm; Simon, Viviana; et al.
Abstract: The coronavirus disease‐2019 (COVID‐19) pandemic is still challenging public health systems worldwide, particularly with the emergence of novel SARS‐CoV‐2 variants with mutations that increase their transmissibility and immune escape. This is the case of the variant of concern Omicron that rapidly spread globally. Here, using epidemiological and genomic data we compared the situations in South Africa as the epicenter of emergence, United Kingdom, and with particular interest New York City. This rapid global dispersal from the place of first report reemphasizes the high transmissibility of Omicron, which needed only two weeks to become dominant in the United Kingdom and New York City. Our analyses suggest that as SARS‐CoV‐2 continues to evolve, global authorities must prioritize equity in vaccine access and continued genomic surveillance. Future studies are still needed to fully unveil the biological properties of Omicron, but what is certain is that vaccination, large‐scale testing, and infection prevention efforts are the greatest arsenal against the COVID‐19 pandemic.